ANALISIS SAFETY FACTOR BH 915 DENGAN PEMBEBANAN RM 1921 DAN EKSISTING TERHADAP DESAIN AWAL JEMBATAN - Dicky Arisikam; Heru Kuswanto; Muhammad Arifudin; Trina Marlina Nurochima (Universitas Widyatama, 2023)
BH 915 is a two-span bridge located at km 396+427 between Stasiun Muaraenim-MuaralawaiDivre III Palembang. The span length of the bridge is 25 m and 50 m with the initial design based on RMBukit Asam. Each bridge will experience a decrease in condition due to increasing age, operating expenses, and environmental conditions. This degradation analysis cannot only be carried out with inspection procedures that produce qualitative values, but also requires quantitative values. Therefore, in the discussion of this paper, it discusses the analysis of the value of the safety factor on the BH 915 bridge due to loading with a combination of dead load and live load in the form of RM 1921 and Existing with a comparison to the initial design of the bridge using RM Bukit Asam loading.From the results of the analysis, BH 915 with a span of 25 m under normal conditions has a safety factor value of 0.91 when loaded with RM 1921, 1.25when loaded with locomotives, 1.58 when loaded with locomotives, and 1.92 when loaded with carriages. BH 915 with a span of 50 m under normal conditions has a safety factor value of 0.89 when loaded with RM 1921, 1.31 when loaded with locomotives, 1.71when loaded with locomotives, and 1.96 when loaded with carriages. When it is assumed that the quality ofthe bridge is reduced by 25% (moment increases by 25%), the value of the safety factor has decreased by 20%.